Effects of Three Types of Oil Dispersants on Biodegradation of Dispersed Crude Oil in Water Surrounding Two Persian Gulf Provinces. (26th January 2012) - Zolfaghari-Baghbaderani, Azadeh; Emtyazjoo, Mozhgan; Poursafa, Parinaz; Mehrabian, Sedigheh; Bijani, Samira; Farkhani, Daryoush; Mirmoghtadaee, Parisa
Abstract : Objective . To determine the most effective and biodegradable dispersant of spilled oil in water surrounding two Persian Gulf provinces. Methods . This study compared the effects of three dispersants, Pars 1, Pars 2, and Gamlen OD4000 on removal of oil in two Persian Gulf provinces' water. Overall, 16 stations were selected. Using the Well method, the growth rate of isolated bacteria and fungi was identified. To specify the growth rate of microorganisms and their usage of oil in the presence of the above-mentioned dispersants, as exclusive sources of carbon, the bacteria were grown in culture medium for 28 days at 120 rpm, 30 ∘ C, and their optical density was measured by spectrophotometry. Then, we tested biological oxygen demand (BOD) and chemical oxygen demand (COD) in microorganisms. Results . The highest growth rate was documented for the growth of microorganisms on either Pars 1 or Pars 2 dispersants or their mixtures with oil. However, the culture having microorganisms grown on Pars 1 had higher BOD and COD than the other two dispersants (9200 and 16800 versus 500 and 960, P < 0.05 ). Mixture of oil and Pars 2 as well as oil and Pars 1 dispersants showed the highest BODs and CODs, respectively. In the Bahregan province, microorganisms grown on Pars 2 had maximum amount of BOD and COD in comparison with Pars 1 and Gamlen dispersants (7100 and 15200 versus 6000 and 10560, P < 0.05 ). Conclusion . Pars 1 and Pars 2 were the most effective dispersants with highest degradability comparing Gamlen. In each region, the most suitable compound for removing oil spill from offshores with least secondary contamination should be investigated.